Eutectic Mixture Formation and Relaxation Dynamics of Coamorphous Mixtures of Two Benzodiazepine Drugs - Sofia Valenti; Claudio Cazorla; Michela Romanini; Josep Lluís Tamarit; Roberto Macovez (MDPI AG, 2023)
The formation of coamorphous mixtures of pharmaceuticals is an interesting strategy to improve the solubility and bioavailability of drugs, while at the same time enhancing the kinetic stability of the resulting binary glass and allowing the simultaneous administration of two active principles. In this contribution, we describe kinetically stable amorphous binary mixtures of two commercial active pharmaceutical ingredients, diazepam and nordazepam, of which the latter, besides being administered as a drug on its own, is also the main active metabolite of the other in the human body. We report the eutectic equilibrium-phase diagram of the binary mixture, which is found to be characterized by an experimental eutectic composition of 0.18 molar fraction of nordazepam, with a eutectic melting point of Te = 395.4 ± 1.2 K. The two compounds are barely miscible in the crystalline phase. The mechanically obtained mixtures were melted and supercooled to study the glass-transition and molecular-relaxation dynamics of amorphous mixtures at the corresponding concentration. The glass-transition temperature was always higher than room temperature and varied linearly with composition. The Te was lower than the onset of thermal decomposition of either compound (pure nordazepam decomposes upon melting and pure diazepam well above its melting point), thus implying that the eutectic liquid and glass can be obtained without any degradation of the drugs. The eutectic glass was kinetically stable against crystallization for at least a few months. The relaxation processes of the amorphous mixtures were studied by dielectric spectroscopy, which provided evidence for a single structural (α) relaxation, a single Johari-Goldstein (β) relaxation, and a ring-inversion conformational relaxation of the diazepinic ring, occurring on the same timescale in both drugs. We further characterized both the binary mixtures and pure compounds by FTIR spectroscopy and first-principles density functional theory (DFT) simulations to analyze intermolecular interactions. The DFT calculations confirm the presence of strong attractive forces within the heteromolecular dimer, leading to large dimer interaction energies of the order of −0.1 eV.